Causality and Nature in the Hippocratic Treatises - Hobza, Pavel (Aither, 2016)
In my paper I am dealing with the problem when and in what form the notion of causality appeared in ancient Greece. It is mostly assumed that already the Presocratics (even the Milesians) dealt with causes. However, none of the extant Presocratic fragments mentions the Greek term for cause (aitia or aition), which is why we should look for the origin of the conception of causality elsewhere. The elaborate conception of causality is to be found in the Corpus Hippocraticum, whose oldest texts originate from the second half of the fifth century B. C. As the close analysis of the Hippocratic treatise On the Sacred Disease suggests, here we find a very complex causal theory articulated by means of the concept phusis. Although there are few occurrences of the term phusis in the Presocratics, they used it only in the common meaning "true nature", not referring to its etymology, i.e. "growth". By exploiting its etymological implications the Hippocratic authors were able to conceive of it as a fundamental causal factor.